The Effect of Price and Product Quality On Purchasing Decisions of Kopi Jago Consumers At Tebet Eco Park - Ahmad Fairuz; Muhammad Aufa Hawa; Ahmad Raihan; Abdurrahman Abdurrahman; Intan Puspita Rini (ICON Publisher, 2026)
This study investigates the impact of price and product quality on consumer purchasing decisions for Kopi Jago at Tebet Eco Park. With growing competition in the coffee industry, businesses must adopt effective marketing strategies, particularly in pricing and product quality enhancement. A quantitative survey approach was employed, targeting consumers who had purchased Kopi Jago products in Jakarta. Using purposive sampling, 40 respondents were selected. Data collection was carried out through questionnaires, and the analysis utilized multiple linear regression, preceded by validity and reliability testing. The findings reveal that price has a positive and significant effect on purchasing decisions, while product quality also shows a positive and significant influence. Together, price and product quality significantly shape consumer purchasing behavior, with the coefficient of determination indicating that a substantial portion of purchasing decisions can be explained by these two variables. The results suggest that maintaining competitive pricing and consistent product quality is crucial for strengthening consumer purchasing decisions in the café industry. This research contributes to marketing management literature, particularly in understanding consumer behavior within the food and beverage sector.